Characterization of the complete chloroplast genome of Oxalis corymbosa DC. (Oxalidaceae), a medicinal plant from Zhejiang Province. Issue 3 (4th March 2021) - Zhou, Manjia; Yan, Meixiu; Ying, Zhiqi; He, Xiangyu; Ge, Yuqing; Cheng, Rubin
Abstract: Oxalis corymbosa DC. is an important medicinal and edible perennial herb belonging to the wood-sorrel family Oxalidaceae. In this study, we report the complete chloroplast (cp) genome sequence of O. corymbosa . The assembled chloroplast genome was 151, 351 bp in length, containing two inverted repeated (IR) regions of 24, 587 bp each, a large single copy (LSC) region of 85, 476 bp, and a small single copy (SSC) region of 16, 701 bp. The genome encodes 128 genes, consisting of 82 protein-coding genes, 37 tRNA genes, eight rRNA genes, and one pseudogene ( ycf1 ). The 82 protein-coding genes encode 25, 751 amino acids in total, most of which use the initiation codon ATG, except rps19 and psbC genes start with GTG. The lengths of the tRNA genes range from 71 bp to 93 bp, with the highest GC content of 62.16% in tRNA-Arg (ACG). The overall GC content of O. corymbosa is 36.47%, with the highest GC content of 42.64% in IR region. In addition, a total of 74 simple sequence repeats were identified in the cp genome of O. corymbosa . Phylogenetic analysis indicated a sister relationship between O. corymbosa and O. drummondii, suggesting a close genetic relationship between the two Oxalis species. This work provides basic genetic resources for investigating the evolutionary status and population genetics diversities for this medicinal species.